Kesulitan Mahasiswa dalam Mata Kuliah Mendengarkan - Wulandari, Ratih Ayu; Sintawati, Fairus (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2021)
Listening plays the most crucial skill since it develops first in people’s language learning process, including foreign language learning process. Listening skill would enable people to improve their ability in communication. However, in some cases of EFL classes, college students still find difficulties in learning the skill since it needs more attentions and concentrations in order to comprehend the language materials. This study tries to discover the listening difficulties encountered by English Education Department students of Faletehan University taking the listening courses. There were 16 students participated in this study. The data was gathered by using questionnaires, interviews, and documentations. The results of the study showed that there are four main categories of students’ difficulties in listening, namely: difficulties related to the learning materials (unfamiliar topics, topic that doesn’t exist in students’ cultures, too many unfamiliar words, and the length of the spoken texts); difficulties related to the speakers (unclear pronunciation, varieties of accents, and the speed of speaking); difficulties related to the listeners (inferring the meanings of unknown words, losing concentration, memory, and the length of the questions); and difficulties related to the physical settings (noises around, the online learning media used, and the internet connection).